Biosimilar strategic implementation at a large health system. (1st November 2021) - Kar, Indrani; Kronz, Margaret; Kolychev, Evelina; Silverman, Paula; Mendiratta, Prateek; Tomlinson, Benjamin K N; Prunty, Jeremy; Copley, Melissa; Patel, Seema; Caudill, Sara; Farah, Lisa; Wesolowski, Bryan; et al.
Abstract: Purpose: This article highlights one health system's response to the market influx of biosimilars with the establishment of a process for formulary review and selection of preferred agents and support for therapeutic interchanges. Summary: Through assessment of available literature, insurance payor coverage, and manufacturer-anticipated approvals of biosimilars, a strategic stance was developed to guide biosimilar order preparation, review, adoption, and implementation. The electronic medical record (EMR) is prepared for biosimilar implementation at least 6 to 12 months ahead of anticipated formulary review. The review includes assessment of a class (reference product and available biosimilars) after at least 2 biosimilars become available. Key health-system departments and clinicians are enlisted to support review of clinical, safety, and economic implications. Implementation of a preferred product relies on standard education, formulary availability, and staff awareness to address any perceived patient safety concerns and gather provider support. The standard steps developed now apply to all future biosimilar reviews, adoption plans, and ongoing monitoring. Barriers evaluated include changes in payor coverage and challenges in preparation of the EMR for future biosimilars, meeting precertification team education needs, and providing operational support for pharmacy inventory. Conclusion: To date, use of 5 preferred biosimilar products has led to significant cost savings to the institution, and the process has been endorsed by providers. The institution's successes can be attributed to clear communication with stakeholders and the development of a deliberate process, led by a multidisciplinary leadership team, for managing formulary, safety, and operational barriers in a thoughtful and systematic manner.